Approaches to the Late Horizon in the Supe and Huaura valleys: Caral, Chimú Cápac and Acaray - Cornejo Guerrero, Miguel Antonio (2023)
This study makes a preliminary characterization of the Late Horizon in the Supe and Huaura valley considering three emblematic sites: Caral, Chimú Cápac and Acaray. An observational methodology was applied, using checklists, archaeological field techniques and cabinet analysis. Some aspects of the Inka, Chimú and Chancay material culture were identified, such as architecture, funerary behavior, ceramic styles involved and a propo- sed sequence of occupation.